Prediction of blood damage within biomedical blood-wetted devices due to mechanical action - Zhanshayeva, L.; Zhussupbekov, M.; Rojas-Solorzano, L. (Nazarbayev University, 2014)
The goal of this project is to develop a CFD model of blood to predict hemolysis due to mechanical action in biomedical blood-wetted devices. Most of the current models approximate blood as a Newtonian fluid at high shear rates. Our work is based on numerical model developed in [1] that modeled blood as a multiphase fluid with constant viscosity. Although successful in capturing phase segregation (Fahraeus-Lindqvist effect), it still did not reach acceptable agreement with experimental data in terms of damage. Gijsen et al. [2] reported significant differences between flow fields obtained by Newtonian and non-Newtonian models of blood. The goal of this study is to introduce non-Newtonian blood rheology to the base model and validate it with existing experimental data.
Keywords: CFD model; biomedical blood-wetted; blood rheology